Antioxidant status, ?-amylase production, growth, and survival of he mioglobin bearing Escherichia coli exposed to hypochlorous acid - Aydin, S (Pleiades Publishing Ltd, 2005)
In the present work, two matched strains of E. coli that bear a recombinant R-amylase gene (MK57) or the R-amylase gene and vgb (MK79-hemoglobin expressing strain) were exposed to HOCl In these cells, glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), (x-amylase production, growth and lethality were assessed in the presence and absence of HOCl It was observed that the hemoglobin makes cells highly susceptible to killing by HOCl The maximum survival for both strains was with stationary phase cells at any concentration of HOCl Both strains grown in the presence of 0.0125-0.075 mg/liter HOCl showed a substantial increase in SOD activity and GSH level, with MK79 being the most increased strain in this respect, while the level of CAT activity was decreased in a dose depended manner. Growth of MK57 and MK79 strains decreased as HOCl concentration increased. However, HOCl at concentration above zero enhanced (alpha-amylase production (about 2-fold) in both MK79 and MK57. Furthermore, total amylase production (at all HOCl concentrations) by MK79 was always greater than that by MK57. The results indicate that except for survival, the hemoglobin helps cells to grow better and produces more recombinant products and activates general defense systems more in response to oxidative stress under oxidative condition when compared with the non-hemoglobin-containing counterpart.
4th Annual World Congress of the Human-Proteome-Organisation (HUPO) -- AUG 28-SEP 01, 2005 -- Munich, GERMANY
Keywords: Escherichia coli; Vitreoscilla hemoglobin; hypochlorous acid; oxidative stress; SOD; catalase; glutathione; alpha-amylase